Digital Image Noise Reduction Application with Mean And Median Filter Method - Rifa Ferawaty Rangkuti (Bahasa Indonesia, 2020)
Images such as photos and so on, for some people are memories that carry a thousand meanings. As mentioned in a word of wisdom, one word only means one word but a picture represents a thousand meanings. Even though at present, the position of the image has been shifted by moving images such as videos, it's just that the use of images as a medium for storing an event remains in a strategic position. In this study, the noise reduction method is used as an image improvement method. Based on the tests carried out, it can be concluded that Noise is an image or pixel that interferes with image quality. The higher the ProbNoise value (noise density) given, the lower the PSNR value produced and the greater the MSE value obtained,